Vortex reversal is a precursor of confined bacterial turbulence - Daiki Nishiguchi; Sora Shiratani; Kazumasa A. Takeuchi; Igor S. Aranson (Proceedings of the National Academy of Sciences, 2025)
Active turbulence, or chaotic self-organized collective motion, is often observed in concentrated suspensions of motile bacteria and other systems of self-propelled interacting agents. To date, there is no fundamental understanding of how geometrical confinement orchestrates active turbulence and alters its physical properties. Here, by combining large-scale experiments, computer modeling, and analytical theory, we have identified a generic sequence of transitions occurring in bacterial suspensions confined in cylindrical wells of varying radii. With increasing the well’s radius, we observed that persistent vortex motion gives way to periodic vortex reversals, four-vortex pulsations, and then well-developed active turbulence. Using computational modeling and analytical theory, we have shown that vortex reversal results from the nonlinear interaction of the first three azimuthal modes that become unstable with the radius increase. The analytical results account for our key experimental findings. To further validate our approach, we reconstructed equations of motion from experimental data. Our findings shed light on the universal properties of confined bacterial active matter and can be applied to various biological and synthetic active systems.